Penerapan Otomasi Dalam Aplikasi Program Barcode Pada Seluruh Design Sticker Cetak Innerbox & Outerbox - Andre Eugenio; Rahmat Saputra (Journal Industrial Manufacturing, 2024)
The efficiency of a PDF-to-auto print sticker can be achieved by using a bar-code program application that offers a more accurate and efficient solution in printing PDF data on labels that allows for accurate, efficient labelling and indication of important information, such as the date and time of preparation and usage, to ensure that the data is not wrong when it reaches the customer.By using a barcode program application such as a sticker/template label, operators can deliver services faster, as well as back offices can track valuable assets and improve process efficiency. Printers, for example, have a wide range of advanced functions and performance in durable and space-saving designs.Thus, the efficiency of PDF-to-auto printing sticker can be achieved by using a barcode application that offers a more accurate and efficient solution in printing PDF data on labels, as well as a thermal transfer printer that has advanced performance and space-saving. Automation in Indonesian can be understood as the use of technology to perform work automatically, without much human intervention.Â Keywords: Efficiency, Automatic.Auto